Quality management in the supply chain integrating the ISO 9001 standard and the PMBOK project guide (LACCEI, 2024)
In modern times, it is very important that organizations prevent delays or deviations in their processes, which is why quality management exists, which is a set of actions and tools that allow a company to guarantee the quality of your products and/or services. The main objective of this research work is to propose a quality management model for the supply chain applying the fundamentals of the PMBOK guide and the ISO 9001 standard. As part of the results obtained through the statistical software SPSS in its version IBM 25 and the observation sheet tool, from the warehouse, dispatch and picking area growth was observed in the post test with an increase from 0.307 to 0.658 achieving a response of almost double that found in the pretest. Also, it was concluded that there was a positive increase of 12.5% at the leadership level, of 8.2% at the planning level and the operation level, it is determined that there was a growth of 17%, granting a better operational maintenance, with which it is stated that there was greater precision in the scope of the integrated model, making visible a continuous improvement in supply chain management.